Stunning fish with CO2 or electricity: contradictory results on behavioural and physiological stress responses. (11th May 2015) - Gräns, A.; Niklasson, L.; Sandblom, E.; Sundell, K.; Algers, B.; Berg, C.; Lundh, T.; Axelsson, M.; Sundh, H.; Kiessling, A.
Abstract : Studies that address fish welfare before slaughter have concluded that many of the traditional systems used to stun fish including CO2 narcosis are unacceptable as they cause avoidable stress before death. One system recommended as a better alternative is electrical stunning, however, the welfare aspects of this method are not yet fully understood. To assess welfare in aquaculture both behavioural and physiological measurements have been used, but few studies have examined the relationship between these variables. In an on-site study aversive behaviours and several physiological stress indicators, including plasma levels of cortisol and ions as well as blood physiological variables, were compared in Arctic char ( Salvelinus alpinus ) stunned with CO2 or electricity. Exposure to water saturated with CO2 triggered aversive struggling and escape responses for several minutes before immobilization, whereas in fish exposed to an electric current immobilization was close to instant. On average, it took 5 min for the fish to recover from electrical stunning, whereas fish stunned with CO2 did not recover. Despite this, the electrically stunned fish had more than double the plasma levels of cortisol compared with fish stunned with CO2 . This result is surprising considering that the behavioural reactions were much more pronounced following CO2 exposure. These contradictory results are discussed with regard to animal welfare and stress physiological responses. The present results emphasise the importance of using an integrative and interdisciplinary approach and to include both behavioural and physiological stress indicators in order to make accurate welfare assessments of fish in aquaculture.